Crystal structure of a birefringent andradite–grossular from Crowsnest Pass, Alberta, Canada. Issue 1 (28th October 2013) - Antao, Sytle M.; Klincker, Allison M.
<x content-type="archive" xml:space="preserve">Abstract</x> The structure of a birefringent andradite–grossular sample was refined using single-crystal X-ray diffraction (SCD) and synchrotron high-resolution powder X-ray diffraction (HRPXRD) data. Electron-microprobe results indicate a homogeneous composition of {Ca2.88Mn2+0.06Mg0.04Fe2+0.03}Σ3[Fe3+1.29Al0.49Ti4+0.17Fe2+0.06] Σ2(Si2.89Al0.11) Σ3O12. The Rietveld refinement reduced χ2 = 1.384 and overall R (F2) = 0.0315. The HRPXRD data show that the sample contains three phases. For phase-1, the weight %, unit-cell parameter (Å), distances (Å), and site occupancy factor (sof) are 62.85(7)%, a = 12.000 06(2), average <Ca–O> = 2.4196, Fe–O = 1.9882(5), Si–O = 1.6542(6) Å, Ca(sof) = 0.970(2), Fe(sof) = 0.763(1), and Si(sof) = 0.954(2). The corresponding data for phase-2 are 19.14(9)%, a = 12.049 51(2), average <Ca–O> = 2.427, Fe–O = 1.999(1), Si–O = 1.665(1) Å, Ca(sof) = 0.928(4), Fe(sof) = 0.825(3), and Si(sof) = 0.964(4). The corresponding data for phase-3 are 18.01(9)%, a = 12.019 68(3), average <Ca–O> = 2.424, Fe–O = 1.992(2), Si–O = 1.658(2) Å, Ca(sof) = 0.896(5), Fe(sof) = 0.754(4), and Si(sof) = 0.936(5). The fine-scale coexistence of the three phases causes strain that arises from the unit-cell and bond distances differences, and gives rise to strain-induced birefringence. The results from the SCD are similar to the dominant phase-1 obtained by the HRPXRD, but the SCD misses the minor phases.